2017
DOI: 10.1002/ange.201700927
|View full text |Cite
|
Sign up to set email alerts
|

A Nickel Dithiolate Water Reduction Catalyst Providing Ligand‐Based Proton‐Coupled Electron‐Transfer Pathways

Abstract: A nickel pyrazinedithiolate ([Ni(dcpdt)2]2−; dcpdt=5,6‐dicyanopyrazine‐2,3‐dithiolate), bearing a NiS4 core similar to the active center of [NiFe] hydrogenase, is shown to serve as an efficient molecular catalyst for the hydrogen evolution reaction (HER). This catalyst shows effectively low overpotentials for HER (330–400 mV at pH 4–6). Moreover, the turnover number of catalysis reaches 20 000 over the 24 h electrolysis with a high Faradaic efficiency, 92–100 %. The electrochemical and DFT studies reveal that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…275 A similar mechanism is thought to enable the promising activity of HEC Ni23 . 277 Using a GC WE in aqueous acetate solution (pH 5.0) at E appl = −0.95 V vs SCE, Ni23 reached a TON H2 of 20 000 with >99% FE H2 over 24 h. DFT showed that only ligand-based reductions occur, along with pyrazine protonation through PCET, resulting in metal-hydride formation without low-valent Ni + or Ni 0 species. 277…”
Section: Homogeneous Catalysismentioning
confidence: 98%
“…275 A similar mechanism is thought to enable the promising activity of HEC Ni23 . 277 Using a GC WE in aqueous acetate solution (pH 5.0) at E appl = −0.95 V vs SCE, Ni23 reached a TON H2 of 20 000 with >99% FE H2 over 24 h. DFT showed that only ligand-based reductions occur, along with pyrazine protonation through PCET, resulting in metal-hydride formation without low-valent Ni + or Ni 0 species. 277…”
Section: Homogeneous Catalysismentioning
confidence: 98%